Analyzing issues on the design, construction, and maintenance of pavements in the Philippines - Biscocho, Maricar R.; Regidor, Jose Regin F.; Constantino, John Michael G. (Quezon City College of Engineering, University of the Philippines Diliman, 2013)
There are many factors that can affect the lifecycle of a road pavement. Varying conditions of pavements along the country are attributed to several factors including design factors such as heavy vehicle traffic, and construction and maintenance practices. Errors in the practice of the application of those factors will reflect to the lifespan of the pavement. Based on the data collected, factors regarding construction practices and quality control, compared to design and maintenance factors are the most frequent cause of pavement defects and deficiencies. Accuracy in the design factors and quality control must be undertaken for the pavement to serve the traffic for which it was designed. Effective road maintenance and rehabilitation work is needed to preserve the pavement from further deterioration.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Pavements -- Service life; Pavements, Asphalt; Pavements, Concrete